Apoptosis in cancer: implications for therapy - Schulze-Bergkamen, Henning; Krammer, Peter H. (Seminars in oncology, 2005)
Resistance towards apoptosis is a key factor for the survival of a malignant cell. Cancer results if there is too little apoptosis and cells grow faster and live longer than normal cells. In addition, defects in apoptosis signaling contribute to drug resistance of tumor cells. Thus, one of the main goals for oncologic treatment is to overcome resistance of tumor cells towards apoptosis. The exciting challenge in oncology is to translate the growing knowledge of apoptotic pathways into clinical applications. In this review we address the role of apoptosis signaling in tumorigenesis and drug resistance of tumor cells and discuss therapeutic approaches interfering with apoptosis pathways.
Gesehen am 02.03.2021